Clinical outcomes and costs of cardiac revascularisation in England and New York state. Issue 1 (3rd January 2018) - Leyva, Francisco; Qiu, Tian; Evison, Felicity; Christoforou, Christopher; McNulty, David; Ludman, Peter; Ray, Daniel
Abstract : Objectives: Healthcare expenditure per-capita in the USA is higher than in England. We hypothesised that clinical outcomes after cardiac revascularisation are better in the USA. We compared costs and outcomes of patients undergoing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in England and New York State (NYS). Methods: Costs and total mortality were assessed using the Hospital Episode Statistics for England and the Statewide Planning and Research Cooperative System for NYS. Outcomes after a first CABG or PCI were assessed in patients undergoing a first CABG (n=142 969) or PCI (n=431 416). Results: After CABG, crude total mortality in England was 0.72% lower at 30 days and 3.68% lower at 1 year (both P<0.001). After PCI, crude total mortality was 0.35% lower at 30 days and 3.55% lower at 1 year (both P<0.001). No differences emerged in total mortality at 30 days after either CABG (England: HR 1.02, 95% CI 0.94 to 1.10) or PCI (HR 1.04, 95% CI 0.99 to 1.09) after covariate adjustment. At 1 year, adjusted total mortality was lower in England after both CABG (HR 0.74, 95% CI 0.71 to 0.78) and PCI (HR 0.66, 95% CI 0.65 to 0.68). After adjustment for cost-to-charge ratios and purchasing power parities, costs in NYS amounted to uplifts of 3.8-fold for CABG and 3.6-fold for PCI. Conclusions: Total mortality after CABG and PCI was similar at 30 days and lower in England at 1 year. Costs were approximately fourfold higher in NYS.